ASSESING FACTORS ASSOCIATED WITH PREVALENCE OF ANEMIA AMONG CHILDREN UNDER FIVE YEARS OF AGE IN PAEDIATRIC WARD AT LIRA REGIONAL REFERRAL HOSPITAL. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Ogwal Emmanuel (Student's Journal of Health Research, 2023)
Background: The objective aimed to assess factors associated with the prevalence of anemia in children under five years of age and specifically to assess sociodemographics, evaluate the level of knowledge of caregivers and determine economic factors associated with anemia in the pediatric ward at LRRH. Methodology: A hospital-based descriptive and cross-sectional design was employed with both quantitative and qualitative data collection methods on a sample size of 96 participants. Results: The findings indicated the overall prevalence of anemia at LRRH to be 70.8 % partitioned as follows; severe anemia at 34.38%, moderate anemia at 19.8%, and mild anemia at 16.67% with most affected age groups being 24-35 months with female gender constituting 86.4% while males' partners had only 13.5%, with majority coming from rural locality that is to say 60.4% compared to urban locality being 39.6%. Conclusion: Anemia prevalence at LRRH amounted to 70.8% and Sociodemographic findings showed mostly young mothers of 14-25 and 26-35 years had anemic children signifying early marriage, about knowledge about anemia, its causes, signs, and symptoms, it revealed the majority of the people were familiar i.e. had prior knowledge about the condition and reported infections and fever as the main cause, most identifiable signs and symptoms as conjunctiva pallor, yellowish discoloration of the eyes and skin respectively and Economic findings showed most respondents had low-income level (50%) leading to the poorer provision of required foodstuff and low quality of living in their families. Recommendations : The GOU through MOH should support regular and routine conduct of prevalence surveys such as a study like this to keep track of its progress and also to invest more in developing its citizens through supporting various Sacco's within